Sosialisasi Bahaya Penyalahgunaan Narkoba bagi Remaja di Desa Kemukus Kabupaten Lampung Selatan - Topani, Iip Nurul (IAI Nasional Laa Roiba Bogor, 2024)
The aim of the activity is to socialize the dangers of drug abuse among teenagers, especially in Kemukus Village, South Lampung Regency, so that teenagers can understand the impacts of drug abuse, both physically and psychologically. Socialization activities use participatory methods, lectures and discussions. The socialization activity was carried out on August 10 2024 with the number of participants taking part in the socialization activity consisting of around 20 people and 1 Village Secretary located at the Kemukus Village Hall. For this reason, through socialization activities on the dangers of drug abuse, it is possible to increase the understanding of teenagers in Kemukus Village regarding the types of narcotics, the impact and abuse of drugs from physical, psychological, educational aspects as well as ways to prevent and control drugs among teenagers. For this reason, this socialization activity can protect the younger generation as the nation's next generation, especially teenagers from Kemukus village, from the dangers of drug abuse.